Age-Related Differences and Reliability of a Field-Based Fitness Test Battery in Young Trained Footballers: The Role of Biological Age - Jose Jimenez-Iglesias; Oliver Gonzalo-Skok; Mario Landi-Fernández; Alejandro Perez-Bey; Jose Castro-Piñero (Life, 2024)
Background: the purpose of this study was to analyze the reliability of a field-based fitness test battery in young trained football players, according to biological age. Methods: 197 young trained football players (12–19 years old) participated in the study. We measured anthropometric measurements (i.e., height, sitting height, length leg, and body mass), a bilateral vertical jumping test (CMJ), a progressive loading test of squats and hip thrust, acceleration and speed tests (10 m and 30 m sprint tests), a change-of-direction ability test (V–cut test), and a cardiorespiratory fitness test (30–15 intermittent fitness test). Statistical data are shown as the mean ± standard deviation by PHV group in tests and retests. Test reliability was assessed through the intraclass correlation coefficient (ICC), with an ICC above 0.9 being considered high. To evaluate accuracy and repeatability, standard error of measurement, coefficient of variation, and minimum detectable change at 90% were determined and Bland–Altman diagrams were used, establishing a statistical significance of p < 0.05. Results: All of the tests showed non-significant differences between the test and retest in the pooled sample (p > 0.05). Furthermore, all of them presented a trivial effect size (<0.2) and high intraclass correlation coefficients (>0.9), which indicates the high reproducibility of the tests, despite some of them presenting a significant difference between trials (i.e., the CMJ, 10 m sprint, V–cut, and squat tests). Low measurement errors were found for all tests (coefficient of variation [CV] = 4.39–9.39), except for the CMJ and the progressive loading test for squat and hip thrust exercises (CV = 12.2–21.11). Similar results were found irrespective of biological age group. Conclusions: All tests were reliable for the pooled sample as well as for the biological age groups.